Švedų-lietuvių kalbų žodynėlis / Svensk-litauiskt lexikon - Dambrauskaitė-Muralienė, Ramunė; Sausverdė, Ērika (Scandinavistica Vilnensis, 2012)
Swedish-Lithuanian Dictionary (Švedų – lietuvių kalbų žodynėlis) is primarily intended for Lithuanian speakers who learn Swedish. The dictionary covers about 6,500 headwords, which form the basic vocabulary of the Swedish language. It gives the basic meanings of the Swedish words, complete forms of inflection and some stylistic details about the headwords. The dictionary includes the following appendices: pronunciation instructions, an overview of Swedish grammar and lists of the most common irregular verbs, names of countries and their inhabitants, as well as the most common Swedish abbreviations.Šis Švedų-lietuvių kalbų žodynėlis skiriamas besimokantiems švedų kalbos. Žodynėlio apimtis – apie 6500 antraštinių žodžių, sudarančių minimalų švedų kalbos žodyninį fondą. Pateikiamos pagrindinės švedų kalbos žodžių reikšmės, visos kaitymo formos ir kai kurios stilistinės nuorodos. Žodynėlį papildo priedai: švedų kalbos tarimo aprašymas, švedų kalbos gramatikos apžvalga, dažniausių švedų kalbos netaisyklingųjų veiksmažodžių formų sąrašas, valstybių ir jų gyventojų pavadinimai, dažniausiai vartojami švedų kalbos sutrumpinimai ir santrumpos.
Keywords: Swedish; Lithuanian; dictionary; pronunciation; irregular verbs; abbreviations